Numerical approach to define a thermodynamically equivalent material for the conjugate heat transfer simulation of very thin coating layers. (December 2020) - Olmeda, P.; Margot, X.; Quintero, P.; Escalona, J.
Highlights: Multi-factorial 1D heat transfer model allows to define thermodynamic properties. Mesh nodes and material thickness are critical to define a good equivalent material. A thick equivalent material behaves thermodynamically similar as a very thin coating. 3D CHT with walls coated with thin insulating layers might be performed. Abstract: The 3D Conjugate Heat transfer (CHT) calculation of the heat transfer from the gas to the walls of a combustion chamber requires very fine meshing, particularly so when the walls are coated with a very thin insulation layer. It is practically impossible to mesh such thin layers for numerical as well as computational cost reasons. In this paper a solution to this problem is presented: an equivalent material layer with a reasonable meshing thickness is defined in such a way that its thermal behavior matches that of the real very thin coating layer. The methodology used to define the thermodynamic properties of the equivalent coating material is based on a combination of a 1D heat transfer model and a multi-factorial sweep of material properties. This equivalent material layer can then be introduced in the 3D CHT calculation instead of the real coating thin layer, and can be adequately meshed to predict with accuracy the heat losses. The approach is illustrated for a real case and a parametric study is performed to evaluate the importance of the number of mesh nodes and the material thickness.